SEISMIC STRATIGRAPHY AND SEDIMENTARY PROCESSES ON THE KURILE BASIN NORTHERN SLOPE (OKHOTSK SEA) - Karp B.Ya.; Karnaukh V.N.; Baranov B.V.; Dozorova K.A. (My University, 2006)
The Kurile Basin in the Okhotsk Sea, northwestern Pacific, is a back-arc basin located west of the Kurile Island Arc. Cenozoic sedimentation on the Kurile Basin northern slope and on the Academy of Science Rise was studied using 2420 km of high-resolution air gun profiles. Late Oligocene-Quaternary sedimentary history of the northern slope and of the Academy of Science Rise includes three major phases. They are characterized by (1) mass wasting during the rift stage of the Kurile Basin, in Late Oligocene-Middle Miocene; (2) bottom current-controlled sedimentation, which led to widespread occurrence of contourite deposits during the second phase in Early Pliocene-Pleistocene; (3) turbidite and hemipelagic sedimentation on the upper slope and drift sedimentation on the Academy of Science Rise during the third phase in Pleistocene-Holocene. Downslope processes predominate on the lower slope. They include large-scale slumping and sliding of sediments. Mass wasting events are possibly triggered by earthquakes or/and gas hydrate decomposition during sea-level lowstands. © 2006 Elsevier B.V. All rights reserved.
Keywords: CONTOURITE DRIFT; KURILE BASIN; MASS WASTING; OKHOTSK SEA; Holocene; Pleistocene; Pliocene; Miocene; Oligocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен